TEACHING READING COMPREHENSION BY USING 3H (HERE, HIDDEN, AND IN MY HEAD) STRATEGY - Angreni, Nina; Wijaya, Bambang; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purpose of this research is to find out the effectiveness of the use of 3H strategy (Here, Hidden, and in my Head) in teaching reading comprehension to the eighth grade students of SMP Negeri 2 Pontianak in academic year 2013/2014. This research was conducted as a quasi-experimental research with the non-equivalent control group design. The sample of this research were class VIIIB as the experimental class and class VIIID as the control class. The data were collected through pre-test and post test by using the essay test consisting of twenty items and were analyzed by using Effect Size (ES) formula. The finding shows that the effect of treatment is 1.53 (> 1.00) or categorized as strong effect. It indicates that the use of 3H strategy is effective in teaching reading comprehension. Keywords: 3H strategy, reading comprehension Abstrak: Penelitian ini bertjuan untuk mengetahui keefektifitan penggunaan strategi 3H (Here, Hidden, and in my Head) dalam pengajaran pemahaman membaca terhadap siswa kelas 8 SMP Negeri 2 Pontianak tahun ajaran 2013/2014. Penelitian ini dilakukan dengan menggunakan metode quasi-eksperimen dengan desainnon-equivalent control group. Sampel penelitian ini terdiri dari kelas VIIIB sebagai kelas eksperimen dan kelas VIIID sebagai kelas kontrol. Data penelitian dikumpulkan melalui pre-test dan post test dengan menggunakan tes esai yang berjumlah dua puluh soal dan data tersebut dianalisa dengan menggunakan rumus ES (tingkat efektifitas). Hasil penelitian menunjukkan bahwa efek dari penggunaan strategi 3H adalah 1.53 (>1.00) atau dikategorikan memiliki efek yang kuat. Hal ini menandakan bahwa penggunaan strategi 3H efektif dalam pengajaran pemahaman membaca. Kata kunci: strategi 3H, pemahaman membaca